2009
DOI: 10.2337/dc09-0288
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid and Development of Type 2 Diabetes

Abstract: OBJECTIVETo systematically evaluate the association between serum uric acid (SUA) level and subsequent development of type 2 diabetes.RESEARCH DESIGN AND METHODSWe searched Medline (31 March from 1966 to 2009) and Embase (31 March from 1980 to 2009) for observational cohort studies examining the association between SUA and the risk of type 2 diabetes by manual literature search. Relative risks (RRs) for each 1 mg/dl increase in SUA were pooled by using a random-effects model. The studies included were stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
421
2
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(463 citation statements)
references
References 34 publications
22
421
2
18
Order By: Relevance
“…Hence, the variations in uric acid level may be due to gender-dependent differences in the range of uric acid. The overall prevalence of hyperuricemia is 28% which is comparable with the results obtained by a study conducted in Nigeria who reported the prevalence rate to be 25% [7] and also with a study conducted by Ito H. in Japan who reported the prevalence to be 25% (9).Hyperuricemia in diabetes mellitus II is also shown by other various studies [16,17,18].In contrast to these findings, some researchers have also shown negative association between uric acid and diabetes. Cook et al explained higher mean serum uric acid values in prediabetic patients than in recently diagnosed diabetics and lower values in diabetics.…”
Section: Discussioncontrasting
confidence: 50%
“…Hence, the variations in uric acid level may be due to gender-dependent differences in the range of uric acid. The overall prevalence of hyperuricemia is 28% which is comparable with the results obtained by a study conducted in Nigeria who reported the prevalence rate to be 25% [7] and also with a study conducted by Ito H. in Japan who reported the prevalence to be 25% (9).Hyperuricemia in diabetes mellitus II is also shown by other various studies [16,17,18].In contrast to these findings, some researchers have also shown negative association between uric acid and diabetes. Cook et al explained higher mean serum uric acid values in prediabetic patients than in recently diagnosed diabetics and lower values in diabetics.…”
Section: Discussioncontrasting
confidence: 50%
“…Since NAFLD is a hepatic manifestation closely related to elevated levels of SUA and insulin resistance, this association has been studied in several studies among T2DM subjects. 12,13 Compared with non diabetic subjects, T2DM are believed to have an increased risk of developing NAFLD, but the true prevalence of the disorder among prediabetic subjects has not been systematically assessed. In addition, so far, population-based data to determine whether SUA and insulin resistance levels are associated with NAFLD in different stages of impaired glucose regulation, in particular prediabetic states, is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Molteplici studi epidemiologici hanno dimostrato che le concentrazioni ematiche di acido urico predicono la progressione della malattia renale cronica (19), lo sviluppo dello stroke (20), e si associano a ipertensione (21), diabete (22), sindrome metabolica (23). La relazione tra acido urico e scompenso cardiaco appare più controversa, con metanalisi che escludono tale agente dai principali determinanti dello scompenso nella popolazione generale (24), mentre al contrario l'uricemia sembra prevedere in maniera efficace la mortalità cardiovascolare, l'infarto del miocardio, lo stroke (25,26).…”
Section: L'iperuricemia è Quindi Un Fattore DI Rischio Cardiovascolare?unclassified